STUDI TRANSFORMASI PASAR TRADISIONAL, OBJEK STUDI PASAR CIPUTAT, KOTA TANGERANG SELATAN - Nelson Antonio Da Silva Pereira; Suryono Herlambang; Parino Rahardjo; Suryadi Santoso (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
Ciputat Market is located at Jalan Aria Putra, near Flyover Ciputat. With land area of 5,670 m2 and building area 14,516 m2, Ciputat market has 4 levels, namely Basement, floor 1, 2nd Floor, and 3rd floor that contains mosque and market management office,  built by the local government of Tangerang Regency in 1992 and managed by the local Government of the trade and Perdindustrian,  of a total of 1,137 stalls and loss of only 441 stalls and 68 loss that are still selling,  the Occupancy rate of Ciputat market is 37%, it is,  estimated that as many as 698 stalls and 167 loss  are closed,  Most traders choose to sell on the ground floor or outside the market building,  ttested from the research is to know the problems that exist in the market of ciputat and know the factors that cause the number of stalls and Loss  are empty in Ciputat market , judging by the accessibility and location around the market, Ciputat market is strategic, Ciputat Market is a  traditional market that the activities of the sellers and their buyers are carried out directly in the form of retail in the meantime or remain with a limited level of service,  authors do some analysis such as policy analysis, location analysis, site analysis, visitor analysis,  management analysis, and  best Practice Analysis with Deskritif method and SWOT method, in orderto know that ciputat market is maintained or do transformation, with the method of transforming the market of Ciputat is the right decision to improve the quality of Ciputat market. Keywords:  traditional market; traditional market management; transformation of traditional marketsAbstrakPasar Ciputat terletak di Jalan Aria Putra, dekat Flyover Ciputat. Dengan luas tanah 5.670 m2 dan luas bangunan 14.516 m2, Pasar Ciputat memiliki 4 level lantai, yaitu lantai Basement, lantai 1, lantai 2, dan lantai 3 yang berisi masjid serta kantor pengelola pasar, Dibangun oleh Pemerintah Daerah Kabupaten Tangerang pada tahun 1992 dan dikelola oleh Pemerintah daerah Dinas perdagangan dan Perdindustrian, Dari total 1.137 Kios dan loss hanya 441 kios dan 68 loss yang masih berjualan, Occupancy rate Pasar Ciputat ini adalah 37% saja, Diperkirakan sebanyak 698 kios dan 167 loss yang tutup, Kebanyakan pedagangg memilih untuk berjualan di lantai dasar atau di luar gedung pasar, tujuan dari penelitian ini adalah untuk mengetahui permasalahan yang ada di  Pasar Ciputat dan mengetahui faktor yang menyebabkan  banyaknya kios dan loss yang kosong di Pasar Ciputat, dilihat dari aksesisibilitas  dan lokasi sekitar pasar, Pasar Ciputat cukup strategis, Pasar Ciputat adalah  Pasar tradisonal yang kegiatan para penjual dan pembelinya dilakukan secara langsung dalam bentuk eceran dalam waktu sementara atau tetap dengan tingkat pelayanan terbatas,  Penulis melakukan beberapa analisis seperti analisis kebijakan, analisis lokasi, analisis tapak, analisis pengunjung, analisis Pengelolaan, dan analisis best practice dengan metode deskritif dan metode SWOT, demi mengetahui apakah Pasar Ciputat tetap dipertahankan atau melakukan transformasi, dengan metode tersebut mentransformasi Pasar Ciputat adalah keputusan yang tepat untuk meningkatkan kualitas Pasar Ciputat.